Improvement of value orientations in the process of forming the professional competence of teachers - Leonidovna Sokolova, Natalia (2021)
This study examines the issues of value orientations of a teacher and their development as an integral part of professional competence. We drew attention to the relationship between the value orientations and the value sphere within the process of teacher’s professional development, the conditionality of professional competence by the value system. The aim of the research is the theoretical and empirical study of value orientations as a component of the professional competence of teachers. Particular attention is paid to the role and significance of creativity in the teaching performance. Based on the analysis of current literary sources, we examined the phenomenon of professional creativity of a teacher, made an attempt to define this concept and considered its structure and structural components. The research methodology and its algorithm were selected due to the purpose of the study. Experimental work included a complex psychological and pedagogical experiment and diagnostics of the stated parameters before and after the implementation of the advanced training. The study was carried out on the basis of the Institute of Foreign Languages of the Federal State Autonomous Educational Institution of Higher Education “The Peoples’ Friendship University of Russia” (RUDN). The results of the study allow us to conclude that there is a significant relationship between the professional creativity of a teacher and the effectiveness of professional performance, which is confirmed by the results of statistical processing of the data obtained. In the Russian psychological and pedagogical literature on the problem of professional competence two basic concepts are discussed, competence and competency. Researchers argue that these concepts are multidimensional and systemic in nature. In Russia, the difference between these concepts is most thoroughly substantiated in the glossary of the Federal State Educational Standard. It is indicated that competencies consist of knowledge, skills and abilities, as well as of practical experience. The ability to apply them in professional activities is called competence.